Documenting and Analyzing Folk Healing Practices in Tabaco City, Albay - Adovo, Arvin Jake; Bagano, Jim Clay; Baetiong, John Paul; Criseno, Francesca Aliana; Epino, Charles Kendrick; Felipe, Carlo Louis; Gono, Rikki Make; Guilanda, Novel Benjamin; Mangaoang, Ethan Ram; Neuda, Jan Alfred; Palaroan, Graciel; Politico, Jeimarson; et al. (Dúnong: UP Diliman Journal of Student Research; Vol 2 (2023), 2025)
Traditional and alternative medicine has always been a curious case. Despite the availability of health centers, clinics, and local hospitals, there is persisting support, reliability in practice, and study on its various mediums. A comprehensive body of literature has already tackled why this is, but not yet on the scale of Tabaco City, Albay. This research attempts to document the practices of Tabaco City’s folk healers, augmenting the scientific, cultural, social, spiritual, and socio-economic aspects of the folk healers’ stories and experiences. The study also analyzes how these practices reinforce folk healing as a powerful alternative to modern healthcare, and in so doing, offer and give light to possible action plans for integrating this unique form of healing into the mainstream healthcare system. The study conducted a semi-structured interview as a data-gathering method with a total of 40 folk healers coming from 23 barangays of Tabaco City using over-the-phone calls and limited on-site assistance. The data gathered were then organized into a matrix and were used to create maps showcasing how the healers relate to space attributes and with other modern healthcare units. It was found that multiple variables factor in toward cementing Tabaco City folk healing as a potent alternative to hospitals such as affordability, convenience, and the cultural elements underpinned in the practice. These variables hopefully foreshadow the possible efforts that can be taken to revolutionize public health care toward ensuring it reaches the outskirts.